Health professionals' perspectives on delivering home and hospital management at diagnosis for children with type 1 diabetes: A qualitative study from the Delivering Early Care in Diabetes Evaluation trial. Issue 5 (30th April 2020) - Townson, Julia; Lowes, Lesley; Robling, Michael; Hood, Kerry; Gregory, John W.
Abstract: Objective: To explore the delivery of home and hospital management at diagnosis of type 1 diabetes in childhood and any impact this had on health professionals delivering care. Methods: This qualitative study was undertaken as part of the Delivering Early Care in Diabetes Evaluation randomized controlled trial where participants were individually randomized to receive initiation of management at diagnosis, to home or hospital. Semi‐structured telephone interviews were planned with a purposive sample of health professionals involved with the delivery of home and hospital management, to include consultants, diabetes and research nurses, and dieticians from the eight UK centres taking part. The interview schedule focused on their experiences of delivering the two models of care; preferences, impact, and future plans. Data were subject to thematic analysis. Results: Twenty‐two health professionals participated, represented by consultants, diabetes and research nurses, and dieticians. Overall, nurses preferred home management and perceived it to be beneficial in terms of facilitating a unique opportunity to understand family life and provide education to extended family members. Nurses described a special bond and lasting relationship that they developed with the home managed children and families. Consultants expressed concern that it jeopardized their relationship with families. Dieticians reported being unable to deliver short bursts of education to families in the home managed arm. All health professionals were equally divided over which was logistically easier to deliver. Conclusions: A hybrid approach, of a brief stay in hospital and early home management, offers a pragmatic solution to the advantages and challenges presented by both systems.